(untitled) (The Batuk, 2026)
Federalism in Nepal, constitutionally adopted in 2015, was envisioned as a transformative framework to promote inclusive governance, address historical inequalities, and catalyze sub national development. The constitutional design emphasizes the devolution of power across three tiers of government with provisions for co-existence, cooperation, and collaboration and aimed at fulfilling development aspirations through equitable resource distribution to marginalized provinces and communities. The article aims to find out the gap between constitutional commitment and the performance of its execution through an extensive review of secondary sources, including academic literature, policy analyses, and empirical studies drawing on relevant theories such as fiscal federalism, center periphery dynamics, and political economic perspectives. The study reveals how federalism’s constitutional promises remain largely unmet by examining critically the persistent sub national underdevelopment particularly in peripheral regions such as Karnali, Sudurpaschim, and Madhesh despite formal federal implementation nearly a decade. This research identifies structural, institutional, and socio-political factors including inadequate fiscal devolution, administrative centralization, political clientelism, gender disparities, and deep-rooted exclusion that have hindered equitable development. The findings underscore the need to strengthen inclusive governance and resource distribution to ensure genuine development and empowerment at the sub national level.